Mucocutaneous mycoses in people living with human immunodeficiency virus in Indonesia. Issue 3 (30th December 2021) - Widaty, Sandra; Oktarina, Caroline; Suling, Pieter Levinus; Niode, Nurdjannah Jane; Miranda, Eliza; Andriani, Anni; Amin, Safruddin; Yenny, Satya Widya; Bramono, Kusmarinah
Abstract: Background: To date, integrated care for people living with human immunodeficiency virus (PLHIV) has improved. However, although the management of mucocutaneous mycosis cases has improved, disease progression might be different in immunocompromised patients, which leads to variable clinical manifestations. Objectives: To describe the characteristics of mucocutaneous mycosis cases in the PLHIV population and its associated factors in Indonesia. Methods: This retrospective study was conducted from January 2014 to December 2018 in four academic hospitals. Data were acquired from medical records with the inclusion of mucocutaneous mycosis patients with concurrent HIV infection. Analysis with the chi‐squared test was performed using Statistical Package for the Social Sciences (SPSS) version 20.0. Results: A total of 1, 796 cases of mucocutaneous mycoses were identified in 1782 PLHIV. The most common types of infection were candidiasis (63%), followed by dermatophytosis (35.1%), and malasseziosis (1.9%), which were significantly higher in PLHIV with CD4 level <200 cells/mm 3 . The proportions of male gender (78.6% vs. 56.3%, p  < .001), high level of education (48.0% vs. 64.1%, p  < .001), office workers (73.8% vs. 64.1%, p  < .001), combination of topical and systemic antifungal agents (59.1% vs. 48.5%, p  = .006) and not receiving antiretroviral therapy (63.2% vs. 7.8%, p  < .001) were significantly higher in PLHIV with a CD4 level <200 cells/mm 3 . Conclusion: In Indonesia, the most common fungal infection in PLHIV is candidiasis. This study also addressed the important matters regarding mucocutaneous mycoses in PLHIV. Education is an important measure to prevent the incidence of cutaneous mycoses in PLHIV, especially in high‐risk groups.